Interaction between tetrathiafulvalene carboxylic acid and ytterbium DO3A: solution state self-assembly of a ternary complex which is luminescent in the near IR. - Faulkner, S; Burton-Pye, B; Khan, T; Martin, L; Wray, S; Skabara, P (2002)
Tetrathiafulvalene carboxylate associates with the charge neutral complex, Yb.DO3A, in methanolic solution to give rise to a novel ternary species; the tetrathiafulvalene unit transfers energy to the lanthanide, causing luminescence from the Yb metal, indicating for the first time that an electron donor chromophore can act as an efficient sensitiser in a self-assembled system containing a lanthanide acceptor.